Building the civic disposition of young citizens in the digital era through civic education courses - Hatami, Wisnu (Universitas Tanjungpura, 2025)
The existence of digitalisation certainly changes the way humans work to be more effective and efficient because it uses various technologies. So, the development of 21st century competencies need to be done by educators to young citizens in order to achieve effective learning objectives. Young citizens need to be given various competencies to become mature citizens. civic disposition is an aspect that needs to be owned by young citizens. This aspect is to make young citizens to become democratic citizens, have responsibility, nationalism and national insight. Currently, there is no research on civic disposition in the digital era in the lecture process. In fact, as a compulsory course, the civics course has an important mission as a personality development course. The research approach used is qualitative with a descriptive study method. Data collection techniques used are observation, interviews, documentation studies and also literature studies. The development of civic education in building the civic character of young citizens in the digital era in higher education can be done by paying attention to lecture materials, media, models, sources and evaluations. While the efforts made by civic education lecturers in overcoming obstacles are in several ways, first by utilising this digital era into civic education lectures. It can be in the form of analysing issues that develop from online media portals, it can also take advantage of citizen projects and be published online through various platforms. The next effort that can be made is by habituating the values of character education during lectures